Neurotransmitters’ Activity and Pharmacotherapies: From Decision Making Process to Juridical Implications - Abdelaziz Ghanemi (Institute of Advanced Engineering and Science, 2013)
Neurotransmitters’ activity, pharmacotherapies, pathological status and the possible interactions between them might influence the neural functions of the brain regions involved in the decision making process. Therefore, we should consider that under certain circumstances, the decision making ability and eventually the behavior might be affected if the individual is for example either under the influence of pharmakons or suffering from neurological disorders. Thus, during legal trials implicating this individual, such approach may have an impact on the juridical decisions or verdicts, especially if it is supported by experts’ opinions on related fields such as pharmacology, toxicology, psychiatry and neuropsychology.